2009
DOI: 10.1038/nature08389
|View full text |Cite
|
Sign up to set email alerts
|

Rapid formation and selective stabilization of synapses for enduring motor memories

Abstract: Novel motor skills are learned through repetitive practice and, once acquired, persist long after training stops 1,2 . Earlier studies have shown that such learning induces an increase in the efficacy of synapses in the primary motor cortex, the persistence of which is associated with retention of the task [3][4][5] . However, how motor learning affects neuronal circuitry at the level of individual synapses and how long-lasting memory is structurally encoded in the intact brain remain unknown. Here we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

78
1,097
8
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,063 publications
(1,219 citation statements)
references
References 31 publications
78
1,097
8
7
Order By: Relevance
“…With respect to spine formation and the size of the forelimb representations in M1, a return to baseline was observed one week after the training ended [5,12]. Thus, in comparison with synapses and motor maps, the plastic modifications of dendritic morphology follow a slower timecourse.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…With respect to spine formation and the size of the forelimb representations in M1, a return to baseline was observed one week after the training ended [5,12]. Thus, in comparison with synapses and motor maps, the plastic modifications of dendritic morphology follow a slower timecourse.…”
Section: Discussionmentioning
confidence: 95%
“…In rodents that learn a motor task [3], plastic changes within M1 have been observed in the form of structural modification in dendrites [4] and their spines [5], in gene expression [6,7], synaptic weights [8] and motor maps [9]. With respect to the temporal profile of plastic changes, an initial phase of growth is followed by a subsequent phase of maturation [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensory manipulation (either enrichment or withdrawal) strongly alters spine dynamics in vivo in various areas of the cortex of adult mice 39 . As a rule, established spines are pruned during the initial experience of the new stimulus, while new ones are established, which may result in some studies of fixed tissue showing no net change in spine density 40, 41 . Consistent with the change in spine dynamics initiated by enrichment, a recent imaging study in the hippocampus identified two phases in spine dynamics following repeated induction of LTP.…”
Section: Discussionmentioning
confidence: 99%